Endoscopic ultrasound-guided choledochoduodenostomy with electrocautery-enhanced lumen-apposing stents: a retrospective analysis - Jacques, Jeremie; Privat, Jocelyn; Pinard, Fabien; Fumex, Fabien; Valats, Jean-Christophe; Chaoui, Azzedine; Cholet, Franck; Godard, Bruno; Grandval, Philippe; Legros, Romain; Kerever, Sebastien; Napoleon, Bertrand (Endoscopy, 2019)
Background Endoscopic ultrasound-guided biliary drainage is an alternative to percutaneous biliary drainage in cases of malignant biliary obstruction and failure of classic endoscopic drainage by endoscopic retrograde cholangiopancreatography (ERCP). Recently, a new electrocautery-enhanced lumen-apposing metal stent (ECE-LAMS) that allows for endoscopic anastomosis (apposition stent) has become available for use in EUS-choledochoduodenostomy (EUS-CDS) and facilitates the procedure.Methods This was a retrospective study of all EUS-CDS procedures performed in France between April 2016 and August 2017. The primary end point was the technical and clinical success rates of EUS-CDS using an ECE-LAMS.Results 52 consecutive patients were included in the study. The etiology of distal bile duct obstruction was distal pancreatic adenocarcinoma in 43 patients (82.7 %). The technical success rate was 88.5 % (46 /52 patients), and the clinical success rate was 100 % (46/46 patients). The mean duration of the procedure was 10.2 minutes (range 1 – 90). Two patients (3.8 %) presented with short-term complications after EUS-CDS and before discharge from hospital. In univariate analyses, a small diameter of the common bile duct and not following the recommended procedure technique were significant risk factors for technical failure. Over a mean follow-up of 157 days, the median survival time without biliary complications was 135 days.Conclusion EUS-CDS with an ECE-LAMS is efficacious and safe in distal malignant obstruction of the common bile duct and could be proposed as the first option in cases of ERCP failure.